(untitled) (Research, Society and Development, 2023)
The present research seeks to analyze how investigative experimentation can contribute to the teaching and learning of Mathematics in the early years of elementary school. Thus, a qualitative approach research was carried out with four regent teachers of a Municipal School in the city of Mãe do Rio (PA). These teachers have experience in classes with students from the 1st to the 5th year of this teaching cycle. As an instrument for data collection, a questionnaire was used, in which professors expressed their contributions based on questions that addressed their academic training, knowledge and use (or not) of investigative experimentation in their practice. The research results showed a lack of knowledge and, consequently, difficulties in using investigative teaching in Mathematics teaching. With this, the need for continuing education processes aimed at the field of active methodologies is highlighted, seeking to broaden the understanding of teachers and contribute to teaching practices based on problem solving, thus bringing scientific content closer to the reality of students.